Design procedures for a passive pyramid solar still with an automatic feed water system - Mahmoud Elgendi; Mohamed Y.E. Selim; Aysha Aldhaheri; Wafa Alshehhi; Houreyah Almarshoodi; Alyaa Alhefeiti (Alexandria Engineering Journal, 2022)
Design procedures are presented here using conceptual design to optimize the performance of a passive pyramid solar still by introducing an automatic feed water system to compensate for the evaporated water from the tank. The procedures may be adopted for passive or active solar still systems. The water level is optimized to be fixed as it shall reduce due to continuous evaporation if no automatic method is used. That will improve the performance of the solar still and increase its output yield. The design procedures considered customer needs which are surveyed and products specifications are decided. Design targets are specified using the quality function deployment. Three design alternatives are proposed and compared, and the best alternative is chosen based on the decision matrix. An auxiliary tank was added between the storage tank and the solar still with a ball valve to maintain a constant water level inside the auxiliary tank and a screw jack to control the elevation of the auxiliary tank and water level. Based on the hydrostatic principle, the elevation of the water level inside the auxiliary tank and solar still must be the same. Therefore, controlling the elevation of the water level inside the auxiliary tank using the screw jack controls the water depth inside the solar still. The proposed feedwater system can maintain the water level inside the solar still to its optimum value that improves the solar still productivity and convenience for the end-user.